The old custom of protecting oneself from the market. Ethnography of an ‘economic process’ among the Nahuas of Huasteca - Claudio Espinoza Araya (CUHSO)
Starting from the ethnographic record of an economic process which occurred in a Nahua communityin Mexico, this article seeks to explore some of the contemporary complexities which accompany the courseof the indigenous peoples of the continent. The problem is addressed by recovering certain elements ofclassic economic anthropology and is centred on the interaction which arises when a micro-credit programmeis introduced into an indigenous community. The case in question serves to demonstrate, once again, thatglobal and national trends end up by being relocated by local actors. It also seeks to remind us that economicmatters may be, and indeed are, subordinate to social.